LncRNA SOX2OT is Upregulated in Gestational Diabetes Mellitus (GDM) and Correlated with Multiple Adverse Events - Ran G; Zhu X; Qin Y (Diabetes, Metabolic Syndrome and Obesity, 2021)
Guangqin Ran, Xiaofan Zhu, Yan Qin Department of Obstetrics and Gynecology, Chongqing General Hospital, University of Chinese Academy of Sciences, Chongqing, 401147, People’s Republic of ChinaCorrespondence: Yan QinDepartment of Obstetrics and Gynecology, Chongqing General Hospital, University of Chinese Academy of Sciences, No. 118, Xingguang Avenue, Liangjiang New Area, Chongqing, 401147, People’s Republic of ChinaTel +86 23-63390545Email yanqinchongqing@163.comPurpose: LncRNA SOX2OT plays protective roles in high glucose-induced injuries, suggesting its potential involvement in diabetes. Therefore, we analyzed the role of SOX2OT in gestational diabetes mellitus (GDM).Methods: A total of 216 pregnant women with a gestational age of about 2 months were enrolled in this study. The 216 pregnant women were monitored until delivery to record the occurrence of GDM. Adverse events, including miscarriage, premature delivery, intrauterine distress, intrauterine death, intrauterine infection, fetal malformation, macrosomia, and hypertension, were recorded.Results: Two hundred sixteen pregnant women were divided into high and low SOX2OT level groups (n=108), with the median plasma SOX2OT level on the day of admission as the cutoff value. It was observed that the incidence of GDM was higher in the high SOX2OT level group (40/108) than in the low SOX2OT level group (12/108). Moreover, the SOX2OT expression level was higher in GDM patients than in non-GDM participants, and ROC curve analysis showed that plasma SOX2OT levels on the day of admission could separate potential GDM patients from the rest participants. Importantly, higher incidences of miscarriage, premature delivery, intrauterine distress, intrauterine death, intrauterine infection, fetal malformation, macrosomia, and hypertension were observed in the high SOX2OT group compared to the low SOX2OT group.Conclusion: SOX2OT is highly expressed in GDM and is closely correlated with multiple adverse events.Keywords: gestational diabetes mellitus, SOX2OT, adverse events